Increased in vitro Anti-HIV Activity of Caffeinium-Functionalized Polyoxometalates - Enderle, Ana Gabriela (2021)
Polyoxometalates (POMs), molecular metal oxide anions, are inorganic clusters with promising antiviral activity. Herein we report increased anti-HIV-1 activity of a POM when electrostatically combined with organic counter-cations. To this end, Keggin-type cerium tungstate POMs have been combined with organic methyl-caffeinium (Caf) cations, and their cytotoxicity, antiviral activity and mode of action have been studied. The novel compound, Caf4K[β2-CeSiW11O39]×H2O, exhibits sub-nanomolar antiviral activity and inhibits HIV-1 infectivity by acting on an early step of the viral infection cycle. This work demonstrates that combination of POM anions and organic bioactive cations can be a powerful new strategy to increase antiviral activity of these inorganic compounds.